ANALISIS POTENSI PAJAK RESTORAN DI KOTA PALEMBANG - Litarani Litarani (Department of Development Economics, Universitas Sriwijaya, 2007)
This research was conducted to find out the potential of the restaurant tax income, efficiency and effectivenees of restaurant tax collection, and the elasticity restaurant tax toward the Gross of Regional Domestic Product sub sector restaurant in Palembang. The data used in this research were primary and secondary data. The primary data was collected from samples; the samples were some restaurants in Palembang. For the secondary data, the writer used the time series long period 1996 to 2006 those were : the Gross of Regional Domestic Product sub sector restaurant and implementation including the target of the tax income toward restaurant in Palembang. The analysis method in finding the potential, efficiency and effectiveness of tax income toward restaurant, the writer used descriptive method. And to find out the score of the elasticity tax of restaurant, the writer used simple regression method. Keywords: tax income, efficiency, effectiveness, elasticity